High-frequency affixed words in BIPA 3 textbooks: a corpus-based study - Fitriyatuz Zakiyah; Asrianti Asrianti (Jurnal Bahasa Indonesia bagi Penutur Asing, 2023)
This study aimed to know the high-frequency affixed words used in BIPA 3 textbooks and the compatibility of the affixes used in BIPA 3 textbooks with SKL BIPA 3. This research used corpus data as the source of the data. The corpus was built from reading texts in BIPA 3 textbooks. The data were analyzed qualitatively to see the high frequency of affixation used in the BIPA 3 textbook and its suitability with the BIPA SKL. The results indicated that there were three types of affixations used in the book. Those were prefix, suffix, and confix. The most common affixation was prefix me- while suffix was rarely used. The affixations in the textbooks followed SKL BIPA 3. However, there were several affixes had been taught at the previous level. Some affixes were not included in BIPA 3 material or even the previous levels.